Low-Power Pervasive Wi-Fi Connectivity Using WiScan - Li, Tianxing; An, Chuankai; Chandra, Ranveer; Campbell, Andrew T.; Zhou, Xia (International Joint Conference on Pervasive and Ubiquitous Computing (UbiComp 2015), 2015)
Pervasive Wi-Fi connectivity is attractive for users in places not covered by cellular services (e.g., when traveling abroad). However, the power drain of frequent Wi-Fi scans undermines the device’s battery life, preventing users from staying always connected and fetching synced emails and instant message notifications (e.g.,WhatsApp). We study the energy overhead of scan and roaming in detail and refer to it as the scan tax problem. Our findings show that the main processor is the primary culprit of the energy overhead. We propose a simple and effective architectural change of offloading scans to the Wi-Fi radio. We design and build WiScan to fully exploit the gain of scan offloading. Our experiments demonstrate that WiScan achieves 90%+ of the maximal connectivity, while saving 50-62% energy for seeking connectivity.